DI (Differentiated Instruction) Does Matter! The Effects of DI on Secondary School Students’ Well-Being, Social Inclusion and Academic Self-Concept - Pozas, Marcela; Letzel, Verena; Lindner, Katharina-Theresa; Schwab, Susanne (Frontiers in Education, 2021)
In consideration of the substantial increase in students’ learning demands, teachers are urged to address student heterogeneity in their daily teaching practice by means of differentiated instruction (DI). The practice of DI, as a vehicle to achieve inclusive education, not only aims to support all students’ academic learning but also foster their social and emotional development. However, current research in the field of DI has mostly been limited to an examination of its effects on students’ achievement outcomes. Consequently, the potential impact of DI on students’ socio-emotional outcomes has, till now, received very little attention. In order to address this gap in the research, the current researchers seek to investigate the effects of DI on school students’ well-being, social inclusion and academic self-concept. Survey participants in this study included 379 students from 23 inclusive and regular classes in secondary schools in Austria. Following multilevel analyses, the results have indicated that students’ rating of their teachers’ DI practice is positively associated with their school well-being, social inclusion and academic self-concept. However, a t-test for dependent samples demonstrated that students perceive their teachers’ DI practice to be infrequent. Implications of the results along with further lines of research are also presented in this paper.